EFFECTIVENESS OF ASSET MANAGEMENT IN THE PUBLIC SECTOR WITH THE APPLICATION OF ASSET MANAGEMENT, ACCOUNTABILITY, MONITORING AND EVALUATION, AND QUALITY OF HUMAN RESOURCES (Case Study in Government of Blitar City-East Java) - Kusnawati, Erlin Ferida; Amartur, Khishigjargal; Armanu, Armanu; Hadiwidjojom, Djumilah (Universitas Brawijaya, Indonesia, 2019)
The purpose of this study is to find out the effectiveness of asset management conducted by Blitar Government using quantitative methods. The type of research used was explanatory research, which explains the effect of Asset Management, Public Accountability, Monitoring, and Evaluation on the Effectiveness of Regional Asset Management that is moderated by Human Resources (HR). Data taken in this research were primary data, secondary data. Those were analyzed using PLS (Partial Least Square), a variance-based structural equation analysis (SEM) that can test the measurement model simultaneously as well as a structural test model. The results of this study indicate that the implementation of asset management affects the effectiveness of asset management. Monitoring and evaluation are important parts of good management practices; therefore, they were an integral part of management.